2020
DOI: 10.1175/jcli-d-19-0454.1
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Relationships of Northwest China Wintertime Precipitation with ENSO and Midlatitude North Atlantic SST since the Mid-1990s

Abstract: The present study investigates the interdecadal changes in the relationship between El Niño–Southern Oscillation (ENSO) and midlatitude North Atlantic (MNA) sea surface temperature (SST) with northwest China (NWC) winter precipitation (WP) variability and the plausible causes. Results show that ENSO and MNA SST have weak correlations with NWC WP before the mid-1990s, whereas the connections are enhanced sharply afterward, with above (below) normal precipitation occuring when there are positive (negative) ENSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Our results suggest that enhanced Indian Ocean SSTs, enhanced Pacific Ocean SSTs, and weakened Asian summer winds contribute to the warming and humidification trend in eastern Xinjiang. This further supports the linkage of Indian Ocean SSTs [33,34], Pacific Ocean SSTs [35,36], and monsoon winds [37,38] with warming and humidification across the northwest. Meanwhile, understanding the influence mechanism of regional precipitation in eastern Xinjiang leads to a more accurate reference value for guiding local water resources management [39] as well as agricultural and livestock production [40].…”
Section: Driving Mechanism Of Precipitationsupporting
confidence: 72%
“…Our results suggest that enhanced Indian Ocean SSTs, enhanced Pacific Ocean SSTs, and weakened Asian summer winds contribute to the warming and humidification trend in eastern Xinjiang. This further supports the linkage of Indian Ocean SSTs [33,34], Pacific Ocean SSTs [35,36], and monsoon winds [37,38] with warming and humidification across the northwest. Meanwhile, understanding the influence mechanism of regional precipitation in eastern Xinjiang leads to a more accurate reference value for guiding local water resources management [39] as well as agricultural and livestock production [40].…”
Section: Driving Mechanism Of Precipitationsupporting
confidence: 72%
“…These results also support that tropical Atlantic SSTAs should be paid more attentions. Yin and Zhou (2020) have investigated winter rainfall in Northwest China and possible impact of ENSO and mid‐latitude NA (30°N–50°N, 60°W–30°W) SSTAs, not for SC rainfall. It is found that the enhanced negative relationship between ENSO and mid‐latitude NA SSTAs after mid‐1990s can excite a Pacific‐North American–Eurasian‐like pattern independently, causing significant precipitation anomalies in Northwest China.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Summer precipitation in EP El Niño years showed a three poles structure of rising in the north and south, but falling in center, while in central Pacific (CP) El Niño years, precipitation was mainly rising [27]. Many scholars have proposed that the correlation between precipitation and ENSO in China, including central [28,29], northwestern [30], northeastern [31], etc., was weak as a whole before the 1990s. After being affected by the change of the Philippine anticyclone [26], the warming of the tropical Indian Ocean [31], the phase anomaly of the sea temperature, and the change of the walker circulation, it significantly intensified [28].…”
Section: Introductionmentioning
confidence: 99%